PELAKSANAAN PERLINDUNGAN HAK ANAK YANG BERKONFLIK DENGAN HUKUM TENTANG BANTUAN HUKUM PADA TINGKAT PENYIDIKAN DI POLRESTA PADANG - Fairus Hanna Pertiwi dan Fitra Oktoriny (Normative Jurnal Ilmiah Hukum, 2019)
Law Number 11 of 2012 concerning the Child Criminal Justice System will provide a new understanding that can be a way out for the problems of Indonesian children, where law enforcement officials are demanded to be more wise in understanding and interpreting cases of child offenders. Legal aid is an embodiment of Human Rights (HAM) including the rights of children in it, so children as perpetrators of crime are entitled to legal protection in accordance with Article 3 of Law Number 11 Year 2012 concerning the Criminal Justice System for Children. The author uses empirical juridical research methods that are descriptive, the type of data used is primary data and secondary data. Based on the discussion, 3 (three) conclusions were drawn, namely, First, the implementation of protecting the rights of children in conflict with the law regarding legal assistance at the level of investigation is not the same as resolving adult cases. In assisting children in conflict with the law, they are accompanied by legal advisors, parents and Bapas. Secondly, the obstacles come from investigators from Padang Police, the community, families of children in conflict with the law, children in conflict with the law and community leaders. Third, the effort to overcome the obstacle is that the investigator tries as much as possible to resolve the case even though in a short time, inadequate facilities can be carried out immediately because it is in the construction stage and when the investigator uses the official attributes which can disrupt the psychological child, the community believes that the offender's child a criminal act is a bad person so it is explained to the public that the child as the perpetrator of the crime is not the same as an adult, the family of the offender who protects his child when the arrest is notified to his family as well, when in the examination the child gives a convoluted statement then the examination is carried out in very different ways and community leaders who were absent were given an invitation letter and the letter explained the purpose of the diversion process.